2011
DOI: 10.1186/1472-6785-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Ancient feeding ecology inferred from stable isotopic evidence from fossil horses in South America over the past 3 Ma

Abstract: BackgroundStable isotope ratios (13C/12C and 18O/16O) in fossil teeth and bone provide key archives for understanding the ecology of extinct horses during the Plio-Pleistocene in South America; however, what happened in areas of sympatry between Equus (Amerhippus) and Hippidion is less understood.ResultsHere, we use stable carbon and oxygen isotopes preserved in 67 fossil tooth and bone samples for seven species of horses from 25 different localities to document the magnitude of the dietary shifts of horses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 52 publications
1
12
0
5
Order By: Relevance
“…Among the South American species classified as grazers, the gomphotheres Cuvieronius hyodon and Stegomastodon waringi , various equids and both toxodontid species all showed quite variable C 4 /C 3 plant proportions in different regions of their distribution ranges, indicating some dietary flexibility (Sánchez et al ., ; MacFadden, ; Prado et al ., ). Although C. hyodon exhibited relatively low‐crowned dentition, carbon isotope analysis indicated that its diet in Bolivia was drawn largely from C 4 grasses (MacFadden & Shockey, ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Among the South American species classified as grazers, the gomphotheres Cuvieronius hyodon and Stegomastodon waringi , various equids and both toxodontid species all showed quite variable C 4 /C 3 plant proportions in different regions of their distribution ranges, indicating some dietary flexibility (Sánchez et al ., ; MacFadden, ; Prado et al ., ). Although C. hyodon exhibited relatively low‐crowned dentition, carbon isotope analysis indicated that its diet in Bolivia was drawn largely from C 4 grasses (MacFadden & Shockey, ).…”
Section: Resultsmentioning
confidence: 97%
“…The even larger S. waringi likewise showed variable C 3 /C 4 plant proportions, despite exhibiting the extreme hypsodonty typical of a grazer (Sánchez et al ., ). Equids in the genus Hippidion showed higher C 3 plant proportions in their diets than Equus spp., but nevertheless had equally high‐crowned dentition, indicating latitudinal or elevational differences in where they grazed (Prado et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Prado et al . ). In this paper, we revise the latest information about the systematics, biogeography and ecology of these groups during the late Cenozoic in South America.…”
Section: Introductionmentioning
confidence: 97%
“…En contraste, las especies de gonfoterios de finales del Pleistoceno parecen tener una dieta menos especializada con una combinación de plantas C 3 y C 4 , que está en consonancia con los supuestos de la hipótesis del mosaico de nutrientes, pero no admite los supuestos de la hipótesis de desequilibrio Co-evolutivo. saldiasi) utilized the Andes corridor, whereas the large forms of these groups (Stegomastodon waringi, Stegomastodon platensis, Equus neogeus and Hippidion principale) utilized the Eastern route and some coastal areas. The route of each form seems to reflect an adaptive shift in their ecology (Alberdi & Prado, 1992;Sánchez et al, 2004;Prado et al, 2011).…”
Section: Introductionunclassified